2012
DOI: 10.1071/ch12190
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Transition Metal Ethyne-1,2-diyl Complexes

Abstract: The chemistry and reactivity of ethyne-1,2-diyl compounds, LnM–CC–MLn, is reviewed. These complexes are simple analogues of organic alkynes, or dimetalloalkynes, and there appears to be no general route to the preparation of these complexes, except perhaps using acid/base methodology. Reactivity patterns, in general, mimic those of simple organic alkynes but have the added dimension of reactive M–C(sp) bonds that sometimes participate in the formation of multimetallic compounds with metal electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 220 publications
1
3
0
Order By: Relevance
“…The structural determination revealed that the cation is comprised of a single Ag + atom coordinated in an essentially symmetrical η 2 fashion to the CC units of two ethyne-1,2-diyl ligands with an average Ag–C distance of 2.321(3) Å. This distance compares well with the average Ag–C distances reported for [Ag­({Re­(CO) 5 } 2 (η 2 -CC)) 2 ]­(SbF 6 ) (2.25(1) Å) and [Ag­(Re­(CO) 3 (bpy)­(η 2 -CCPh)) 2 ]­(PF 6 ) (2.32(6) Å). , The ethyne-1,2-diyl ligands lie almost perpendicular to each other (87.2(4)°) imparting a pseudotetrahedral geometry about the silver atom. The measured CC bond lengths of 1.230(4) and 1.222(4) Å are not appreciably elongated from those of 1a , b and are closely comparable to those of the previously discussed adducts. , The deviations from linearity for the ethyne-1,2-diyl ligands are significantly less than those recorded for 2b and 3a , b with angles of 171.5(3), 168.3(3), 169.4(3), and 170.1(3)° for the Ru(1)–C(1)–C(2), Ru(2)–C(2)–C(1), Ru(3)–C(3)–C(4), and Ru(4)–C(4)–C(3) vectors, respectively.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The structural determination revealed that the cation is comprised of a single Ag + atom coordinated in an essentially symmetrical η 2 fashion to the CC units of two ethyne-1,2-diyl ligands with an average Ag–C distance of 2.321(3) Å. This distance compares well with the average Ag–C distances reported for [Ag­({Re­(CO) 5 } 2 (η 2 -CC)) 2 ]­(SbF 6 ) (2.25(1) Å) and [Ag­(Re­(CO) 3 (bpy)­(η 2 -CCPh)) 2 ]­(PF 6 ) (2.32(6) Å). , The ethyne-1,2-diyl ligands lie almost perpendicular to each other (87.2(4)°) imparting a pseudotetrahedral geometry about the silver atom. The measured CC bond lengths of 1.230(4) and 1.222(4) Å are not appreciably elongated from those of 1a , b and are closely comparable to those of the previously discussed adducts. , The deviations from linearity for the ethyne-1,2-diyl ligands are significantly less than those recorded for 2b and 3a , b with angles of 171.5(3), 168.3(3), 169.4(3), and 170.1(3)° for the Ru(1)–C(1)–C(2), Ru(2)–C(2)–C(1), Ru(3)–C(3)–C(4), and Ru(4)–C(4)–C(3) vectors, respectively.…”
Section: Resultssupporting
confidence: 64%
“…This distance compares well with the average Ag−C distances reported for [Ag({Re(CO) 5 } 2 (η 2 -CC)) 2 ](SbF 6 ) (2.25(1) Å) 31 and [Ag(Re(CO) 3 (bpy)(η 2 -CCPh)) 2 ](PF 6 ) (2.32(6) Å). 31,32 The ethyne-1,2-diyl ligands lie almost perpendicular to each other (87.2(4)°) imparting a pseudotetrahedral geometry about the silver atom. The measured CC bond lengths of 1.230(4) and 1.222(4) Å are not appreciably elongated from those of 1a,b and are closely comparable to those of the previously discussed adducts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an initial irreversible oxidation process at −5 mV ( vs FcH/FcH + ; Fc=ferrocenyl=[Fe(η 5 −C 5 H 5 )(η 5 −C 5 H 4 )]) the voltammetric response is identical to this of butadiyne 6 . This behavior is well described for other acetylene compounds [11,20,52,53] and represents an oxidation induced reductive elimination reaction of the two acetylene ligands at platinum. In addition, an irreversible reduction of the decomposition products (the formed unknown Pt‐compound) is observed at −1170 mV.…”
Section: Resultsmentioning
confidence: 54%